(untitled) (Journal of the College of Basic Education, 2023)
The phenomenon of financial and administrative corruption and its negative repercussions on the national economy is one of the problems that Iraq suffers from after the occupation in 2003 for reasons related to political and factional interests and low levels of oversight in various government institutions. The size of this phenomenon in Iraq and the intertwining of its episodes and the interdependence of its mechanisms to an unprecedented degree has become one of the issues that threaten the process of economic development and reconstruction of Iraq, so this phenomenon has received the attention of researchers and scholars, and opinions have agreed on the need to develop solutions and treatments in order to surround this phenomenon through bold initial steps And our research tagged (financial and administrative corruption in Iraq after the occupation - causes and remedies -), which is based on the hypothesis that (the rampant financial and administrative corruption in Iraq has affected in a clear negative way the performance of the national economy and has become an obstacle in the way of achieving economic development and reconstruction of Iraq.